The Impact of Aerobic Training on Cardiovascular Reactivity to and Recovery From Psychological and Orthostatic Challenge. Issue 2 (February 2021) - Sloan, Richard P.; Shapiro, Peter A.; Lauriola, Vincenzo; McIntyre, Kathleen; Pavlicova, Martina; Choi, Chien-Wen Jean; Choo, Tse-Hwei; Scodes, Jennifer M.
ABSTRACT: Objective: Elevated cardiovascular reactivity to, and reduced recovery from, challenging events may increase the risk of cardiovascular disease, and exercise training may reduce this reactivity. However, in a randomized controlled trial of aerobic versus strength training in sedentary, healthy young adults, we found no training group differences in reactivity or recovery. Because strength training also may have a reactivity-reducing effect, we conducted a secondary analysis of data from another trial, this time with a wait-list control condition. Methods: One hundred nineteen healthy, young, sedentary adults were randomized to a 12-week aerobic training program or wait-list control. Before (T1) and after (T2) training and after 4 weeks of sedentary deconditioning (T3), we measured heart rate (HR), heart rate variability, and blood pressure at rest and in response to and recovery from psychological and orthostatic challenge. Data were analyzed using a group (aerobic versus wait-list) by session (T1, T2, and deconditioning) and by period (baseline, psychological challenge, recovery, standing) three-way analysis of variance with prespecified contrasts. Results: Aerobic capacity significantly increased at T2 and decreased at T3 only in the aerobic training group. The groups did not differ on HR, heart rate variability, or blood pressure reactivity to or recovery from challenge. Without baseline adjustment, there were no significant treatment differences in response to challenges. With baseline adjustment, there were significant treatment by session effects for HR (Cohen d = 0.54, p = .002), systolic blood pressure ( d = 0.44, p = .014), diastolic blood pressure ( d = 0.74, p = .002), and root mean squared successive difference ( d = 0.48, p = .006) reactivity from T1 to T2 only for orthostatic challenge: at T2, reactivity in the aerobic group was nonsignificantly reduced, compared with T1. In the wait-list group, reactivity significantly increased after T1. Conclusions: This study raises further doubt about attenuation of cardiovascular reactivity or enhancement of recovery as a cardioprotective mechanism of aerobic exercise training. Clinical Trial Registration: ClinicalTrials.gov Unique identifier: NCT01335737. Abstract : Supplemental digital content is available in the text.